2010
DOI: 10.1007/s00540-010-0966-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of paravertebral block versus fast-track general anesthesia via laryngeal mask airway in outpatient inguinal herniorrhaphy

Abstract: In outpatient IH, PVB with 0.5% levobupivacaine provided improved recovery, long-lasting analgesia, shorter recovery room stays, and earlier home readiness time than fast-track GA via LMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Compared with fast-track general anesthesia, PVB provides a speedier recovery, longerlasting analgesia, shorter stays in the postanesthesia care unit (PACU), and earlier time to home readiness. 39 Nevertheless, PVB is associated with an overall complication rate of 2.6-5%, including block failure (6.8-10%), hypotension (4.6%), vascular puncture (3.8%), pleural puncture (1.1%), and pneumothorax (0.5%). 40 As PVB cannulae are small, pneumothorax may not always follow even if pleural puncture occurs, and a related pneumothorax is usually small and can be managed conservatively.…”
Section: áHrmentioning
confidence: 99%
“…Compared with fast-track general anesthesia, PVB provides a speedier recovery, longerlasting analgesia, shorter stays in the postanesthesia care unit (PACU), and earlier time to home readiness. 39 Nevertheless, PVB is associated with an overall complication rate of 2.6-5%, including block failure (6.8-10%), hypotension (4.6%), vascular puncture (3.8%), pleural puncture (1.1%), and pneumothorax (0.5%). 40 As PVB cannulae are small, pneumothorax may not always follow even if pleural puncture occurs, and a related pneumothorax is usually small and can be managed conservatively.…”
Section: áHrmentioning
confidence: 99%
“…Seventeen studies used a landmark-guided insertion technique to perform TPVB. Seven of these used a pre-specified distance beyond the transverse process as their endpoint for injection, [17][18][19][20][21][22][23] six studies reported using loss-of-resistance as their endpoint, [24][25][26][27][28][29] and four used a peripheral nerve stimulator to confirm entry into the paravertebral space. [30][31][32][33] Three studies used an ultrasound-guided technique to perform TPVB.…”
Section: Technical Performancementioning
confidence: 99%
“…Agarwal et al 2012 30 Akcaboy et al 2009 22 Akcaboy et al 2010 23 Ak et al 2013 20 Baik et al 2013 34 Bhattacharya et al 2010 24 Bigler et al 1989 27 Borle et al 2014 19 Elbealy et al 2008 25 Fusco et al 2016 36 Hadzic et al 2006 17 Hanoura et al 2013 33 Kaya et al 2014 32 Klein et al 2002 21 Mandal et al 2011 28 Melnikov et al 2012 35 Moawad et al 2013 26 Moussa 2008 18 Naja et al Data analysis Meta-analysis of the data was not performed because of the significant heterogeneity in the included studies with regard to type of surgery, comparator groups and definition, measurement and reporting of analgesic outcomes. A qualitative review was undertaken instead.…”
Section: Technical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, added advantage is it does not have the specific side effects and complications of spinal anaesthesia, like PDPH, spinal hematoma, permanent neurological sequel and transient radiculitis. So the current recommendation of several researchers like T Callesen, H Kehlet, EY Akcaboy, ZN Akcaboy [22,23] and the ''European hernia Society'' (grade A 2009) is to use LA for repair of inguinal hernia if there is no contraindication. But still today spinal and lumbar epidural anaesthesia are very popular with their inherent risks particularly in elderly with comorbid diseases for hernia repair because it is easier and quicker to administer and anaesthesiologists are well trained.…”
Section: Discussionmentioning
confidence: 99%